Drinking and alcohol-related problems among at-risk adolescents: The role of protective behavioral strategies. (March 2021) - Greń, Jakub; Ostaszewski, Krzysztof; Pisarska, Agnieszka; Bobrowski, Krzysztof
Highlights: This study examined the role of PBS use among Polish SEC students. The majority (about 94%) of study participants reported employment of some PBS. The PBS use was associated with reduced risk of drinking and alcohol-related problems. PBS (total scale and LSD subscale) were found as significant moderators. Abstract: Introduction: Protective Behavioral Strategies (PBS) are an alcohol-specific cognitive-behavioral strategies that may be employed before, during and/or after drinking, in order to reduce alcohol consumption and related consequences, particularly in the at-risk populations. Previous research on PBS was limited to North American college students. The purpose of this study was to examine the role of PBS use in a sample of Polish adolescents attending Special Educational Centers (SEC). Method: Data were collected from a nationwide sample of 12–19 year-old (Mean = 15.8; SD = 1.22) students attending SEC in Poland (N = 1585; about 33% female). The self-administered anonymous questionnaires were completed on-site in the SEC. PBS were measured by the authors adaptation of the PBSS-20. Alcohol-related problems were assessed by the Polish adaptation of the measures used in the MINI-KID tool. Alcohol use was measured by a single question on drinking frequency. These two latter variables were measured in the past year timeframe. Hierarchical regression models were used to test the main and interaction effects of employing PBS (total and subscales scores) on alcohol-related problems, after adjusting for demographics (gender, family composition and type of SEC) and alcohol use. Results: The majority (about 94%) of study participants reported employment of some PBS. Regression analyses indicated that PBS use was associated with reduced risk of alcohol use and alcohol-related problems. We found that PBS significantly moderated the relationship between alcohol use and alcohol-related problems, for PBS total scale ( F- change (1, 1555) = 15.96, p  < .001) and one of the PBS subscale: Limiting/Stopping Drinking ( F- change (1, 1555) = 4.80, p  < .029). Findings were discussed within the results of PBS literature and resilience theory framework. Conclusion: The use of PBS helps to reduce alcohol-related problems among adolescents attending SEC. Implementation of tailored interventions that teach PBS among vulnerable adolescents may be an effective way to strengthen adolescent self-protection, reduce risky alcohol use and related negative consequences.